Reconstruction of 56 mandibular defects with autologous compressed particulate corticocancellous bone grafts. Issue 3 (April 2016) - Ferretti, Carlo; Muthray, Enesh; Rikhotso, Ephraim; Reyneke, Johan; Ripamonti, Ugo
Abstract: We retrospectively evaluated the results of particulate corticocancellous bone grafting of mandibular defects. Patients with deficits of mandibular continuity as a result of injuries or resection of disease had the affected segment debrided or resected, followed by placement of a patient-specific reconstruction plate. Eight weeks after resection, it was reconstructed with an autotransplant from the posterior iliac crest. Grafts were deemed successful if the regenerated ossicle (after 6 months' maturation) was adequate to take an osseointegrated fixture at least 10 mm long. Fifty-six patients were treated, of whom 5 were lost to follow-up. The remaining 51 patients were followed up for a mean (SD) of 29 (18) months. The mean (SD) length of the defect was 12.4 (8.4) cm. Of the 51 reconstructions, 43 healed uneventfully and the grafts were deemed successful. Two healed grafts developed recurrent tumour, which required resection of the entire reconstructed area in one, and partial resection in the other. Three patients lost the complete graft from sepsis, and five developed sepsis that required debridement with partial loss of the graft. Two patients in the latter group required a second graft. One patient required an augmentation graft, as the ossicle was not sufficient to take an implant. The technique of staged grafting with particulate corticocancellous bone after moulding of the recipient site with a spacer produces unmatched restitution of mandibular anatomy with low morbidity.